Contingency management for smoking cessation among individuals with type 2 diabetes: protocol for a multi-center randomized controlled feasibility trial - Sydney A. Martinez; Samantha L. Quaife; Afsheen Hasan; Kathryn A. McMillan; Laura A. Beebe; Fiona Muirhead (Pilot and Feasibility Studies, 2020)
Abstract Background Individuals with type 2 diabetes (T2D) who smoke are at increased risk for many types of cancers as well as an accelerated progression of microvascular and macrovascular complications. Smoking cessation is recommended as a standard treatment for T2D; however, individuals with T2D are faced with competing lifestyle changes. Glycemic and blood pressure control often take precedence over smoking cessation, and patients are often unmotivated to quit. Contingency management in combination with standard smoking cessation treatment has been demonstrated to improve cessation outcomes in various populations. The purpose of this randomized controlled feasibility trial is to explore the feasibility of contingency management and biochemical verification using a remote smartphone-based carbon monoxide monitor for smoking cessation among individuals with T2D. Methods A three-arm, randomized controlled feasibility trial will be conducted in two study sites that include the USA and UK. We will recruit 60 participants who will each receive usual care smoking cessation treatment (counseling and nicotine replacement therapy) and be randomized to a short term incentives (6 weeks), long term incentives (12 weeks), or no incentives (control) group. Participants will receive a smartphone and carbon monoxide monitor to complete daily remote assessments throughout the 12 weeks and will complete an exit interview at the end of the study. The primary outcomes for this feasibility study include completion of the protocol and proportion of daily assessments completed. Secondary outcomes include recruitment measures, acceptability, and smoking abstinence. Discussion We will explore the feasibility of recruiting smokers with T2D and their engagement in the program, particularly related to the use of the remote biochemical verification and smartphone application. In addition, we will evaluate the intervention content, study procedures, data collection methods, and follow-up and will qualitatively assess the participants’ acceptability of the program. The results of this study will inform the design of a larger trial to test the efficacy of the contingency management program for improving smoking cessation outcomes among individuals with T2D. Trial registration This randomized controlled feasibility trial has been registered at ClinicalTrials.gov with an ID NCT03527667 on May 4, 2018.